International law and the public how ordinary people shape the global legal order - Wallace, Geoffrey P. R. 1978- (Ithaca Cornell University Press, 2024)
"This book investigates the public as a crucial - yet often overlooked - actor in international law compared to the conventional focus on elites. Integrating insights across numerous fields and leveraging an array of evidence, the book demonstrates that ordinary people have an extensive impact on the operation of international legal commitments"--
What is International Law and What Does It (Supposedly) Do? Definition and Functions-- The Operation of International Law : From Top to Bottom . . . And Back Up Again-- Reputation and Enforcement I : Experimental Evidence that Image is Something (but Not Everything)-- Reputation and Enforcement II : The United States, the Laws of War, and the War on Terror-- From Law to Preferences I : Experimental Evidence of a Tortured Relationship-- From Law to Preferences II : Droning on About War-- Conclusion : Understanding the Public and International Law.
Includes bibliographical references (pages 307-347) and index.
Keywords: Effectiveness and validity of law; International law -- Social aspects -- United States; International law -- United States -- Psychological aspects; International law -- United States -- Public opinion